Análisis de combustibles fósiles en el mercado de generación de energía eléctrica en Colombia: Un contraste entre modelos de volatilidad - Mónica Andrea Arango Arango; Santiago Arroyave O. (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– The importance of the electricity sector in the growth of economies encourages the study of the variables that determine the implementation of new investment projects in the sector. The barriers in the availability of fuels result in increased uncertainty, becoming a key issue in making decisions in the markets for power generation. Regarding this, a contrast is performed between a deterministic volatility model and two parametric stochastic volatility models, GARCH and EWMA, applied to the price of fossil fuels, in order to identify trade off between cost and risk faced by generators in an energy matrix comprised of technologies based on coal, gas and oil. The three models allow to compare the empirical results for covariances obtained through Pearson's methodology, EWMA and Vech. Evidence suggests that, in a context where it is necessary to select one of the fuels, coal has less exposure and less variation in price, implying a lower discharge in generation markets. However, having the energy matrix formed by the three fossil fuels allows a lower risk exposure to the global market.
Keywords: N70; C53; C58; P28; 330; energy markets; econometric modeling